Meta-Analysis of Efficacy From CTLA-4 and PD-1/PD-L1 Inhibitors in Cancer Patients - Xu, Li; Yan, Xin; Ding, Weiyue (Frontiers in Oncology, 2022)
Introduction: Immune checkpoint inhibitors (ICIs) have been approved to prolong overall survival (OS), compare to other treatments. However, the recent studies reported consistent and inconsistent results. Hence, we conducted this meta-analysis to evaluate the efficacy of ICIs. Materials and Methods: The articles were identified by searching the PubMed, Embase and Google Scholar published up to November 2017. A total of 9165 participants (5210 cases and 3955 controls) were involved in the meta-analysis. Median OS and median progression-free survival (PFS) were selected to evaluate the efficacy of cytotoxic Tlymphocyte-associated protein 4 (CTLA-4), programmed cell death 1 (PD-1) and programmed death ligand 1 (PD-L1) inhibitors (ipilimumab, nivolumab or pembrolizumab, and atezolizumab, respectively). Utilizing random effect model and fixed effect model, hazard ratios (HRs) with 95 confidence intervals (CIs) were calculated by R software. Results: We observed a significant association between cancer patients and ICIs in OS (HR=0.77, CI= 0.73-0.81) and PFS (HR=0.81, CI= 0.75-0.88). Conclusions: The meta-analysis suggested that ICIs were associated with obvious improvements in PFS and OS compared with non-ICI therapies.